2015
DOI: 10.1111/cen3.12213
|View full text |Cite
|
Sign up to set email alerts
|

Combined nerve/muscle/skin biopsy could increase diagnostic sensitivity for vasculitic neuropathy

Abstract: Objective Combined nerve/muscle biopsy is widely carried out to improve the diagnostic sensitivity for vasculitic neuropathy. However, an additional yield of muscle biopsy is modest. Therefore, we investigated whether skin biopsy in combination with nerve/muscle biopsy increases the detection rate of vasculitis. Methods A total of 25 combined nerve/muscle/skin biopsy samples from patients with biopsy-proven necrotizing vasculitis (n = 16) or clinically probable vasculitic neuropathy (n = 9) were reviewed. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Biopsy of non‐nerve tissue can strengthen the evidence for vasculitis, particularly when there is evidence of systemic vasculitis . In one small study of patients with biopsy‐proven peripheral nerve vasculitis or clinically probable vasculitis, cutaneous vasculitis was identified in some patients without nerve or muscle biopsy evidence of vasculitis, suggesting that concomitant full‐thickness skin biopsy may increase diagnostic yield . Another small study of patients with sural nerve biopsy‐proven NSVN showed that quantification of perivascular macrophages on skin punch biopsies had a sensitivity of 94% and specificity of 79% for NSVN using a cut‐off of 2.9 macrophages per vessel .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsy of non‐nerve tissue can strengthen the evidence for vasculitis, particularly when there is evidence of systemic vasculitis . In one small study of patients with biopsy‐proven peripheral nerve vasculitis or clinically probable vasculitis, cutaneous vasculitis was identified in some patients without nerve or muscle biopsy evidence of vasculitis, suggesting that concomitant full‐thickness skin biopsy may increase diagnostic yield . Another small study of patients with sural nerve biopsy‐proven NSVN showed that quantification of perivascular macrophages on skin punch biopsies had a sensitivity of 94% and specificity of 79% for NSVN using a cut‐off of 2.9 macrophages per vessel .…”
Section: Discussionmentioning
confidence: 99%
“…18 In one small study of patients with biopsy-proven peripheral nerve vasculitis or clinically probable vasculitis, cutaneous vasculitis was identified in some patients without nerve or muscle biopsy evidence of vasculitis, suggesting that concomitant full-thickness skin biopsy may increase diagnostic yield. 19 Another small study of patients with sural nerve biopsy-proven NSVN showed that quantification of perivascular macrophages on skin punch biopsies had a sensitivity of 94% and specificity of 79% for NSVN using a cut-off of 2.9 macrophages per vessel. 20 Quantifying scattered macrophages in skin biopsy may differentiate vasculitis from controls and other axonal neuropathies, with one study demonstrating sensitivity of 71% and specificity of 79% using a cut-off of 13 macrophages/mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of improving diagnostic yield, a small study performed combined nerve/muscle/skin biopsy through a single incision in patients suspected to have vasculitic neuropathy 31 . Among patients without evidence of definite or probable vasculitis on nerve and muscle biopsy, cutaneous vasculitis was identified in 20%.…”
Section: Methodsmentioning
confidence: 99%
“…A biopsy of the peroneus brevis muscle is occasionally carried out in addition to a sural nerve (or superficial peroneal nerve) biopsy to improve the diagnostic accuracy; however, a substantial percentage of possible vasculitic neuropathy patients remained undiagnosed even after this combined nerve/muscle biopsy . In this issue of the journal, Masuda et al . described the merit of a skin biopsy in addition to a nerve/muscle biopsy in the detection of vasculitis.…”
mentioning
confidence: 99%
“…A biopsy of the peroneus brevis muscle is occasionally carried out in addition to a sural nerve (or superficial peroneal nerve) biopsy to improve the diagnostic accuracy; however, a substantial percentage of possible vasculitic neuropathy patients remained undiagnosed even after this combined nerve/muscle biopsy. 1 In this issue of the journal, Masuda et al 2 described the merit of a skin biopsy in addition to a nerve/muscle biopsy in the detection of vasculitis. Although there were no statistical differences between the sensitivity of the nerve/muscle biopsy and that of the nerve/muscle/skin biopsy, vasculitic changes were detected only in the skin biopsies of two in their entire cohort, showing an increase of diagnostic sensitivity by 12%.…”
mentioning
confidence: 99%